Rural Nurse Practitioner Role to Improve Outcomes for Thames-Coromandel Community - Gubb, Alicia (Auckland University of Technology, 2020)
The Nurse Practitioner (NP) role is essential in the future evolution of health care delivery in New Zealand. This role has the potential to achieve more equitable outcomes for rural populations who experience lower access to health care than those living in urban areas. Unmet health needs and suboptimal quality of care lead to older adults in New Zealand experiencing high readmission rates. The transition between hospital and community represents a vulnerable time. Older adults face challenges with physical and cognitive decline and often experience comorbidities and polypharmacy. Nurse practitioners have an advanced scope of practice and provide high quality, personalised care suggesting their potential to improve outcomes for older adults in their transition in the rural setting. By using a realist synthesis approach to review published literature, this research examines how the NP role works in reducing readmissions. The findings formulate insight and recommendations for improving outcomes in the Thames-Coromandel rural community. Realist evaluation principles inform realist synthesis, and these are grounded in the ontological position of realism. Realist synthesis is concerned with developing a programme or systems theory based on context, mechanism, and outcome patterns. In this realist synthesis, the relationship between context, mechanism and outcome provides a theory of generative causation for the NP role in reducing readmissions. The literature search strategy returned 29 articles that met the inclusion criteria and were analysed using Braun and Clarke’s thematic analysis method. Three themes developed from the thematic analysis: self-efficacy in the home, holistic needs met through coordinated interdisciplinary care, and [care] grounded in nursing philosophy. These themes come together to form a theory of generative causation that shows NP led interdisciplinary care provides several effective interventions improving resources and opportunities available to older adults enabling improvement in self-efficacy. This increase in self-efficacy results in older adults being able to effect positive health changes, seek care and escalate concerns early resulting in health being maintained during and after transition from hospital, thereby reducing readmissions. Care provided in the home and care grounded in nursing philosophy trigger the mechanism of self-efficacy. The social cognitive theory of Bandura supports that self-efficacy is required for patients to translate knowledge into improved health outcomes. Understanding this mechanism of self-efficacy is a significant finding in developing strategies for reducing readmissions in older adults and highlights the suitability of NP led models. Connecting, communicating, and coordinating were crucial features of the NP role and in the rural setting innovative measures, such as virtualisation, are needed to enable these. The nursing philosophy of care that is inherent in the NP role supports care delivery to be patient-centred, holistic, and delivered through effective therapeutic relationships. Introducing the NP role in rural communities to improve the transition of older adults between care settings has the potential to decrease readmissions and improve the health and self-efficacy of older adults.
Keywords: Nurse practitioner; Rural; Transitional care; Readmission; Older adult; Self-efficacy; Realist synthesis